Implication of fibroblast growth factor 7 in ovarian cancer metastases and patient survival - Mortan, Laura F.; Meelheim, Brooke A.; Garland, Justin; Bohn, Jacqueline A.; Isingizwe, Zitha Redempta; Benbrook, Doris M. (Frontiers in Oncology, 2025)
Background/ObjectivesPatients with ovarian cancer commonly experience metastases and recurrences, which contribute to high mortality. Our objective was to better understand ovarian cancer metastasis and identify candidate biomarkers and drug targets for predicting and preventing ovarian cancer recurrence.MethodsTranscripts of 770 cancer-associated genes were compared in cells collected from ascitic fluid versus resected tumors of an ES-2 orthotopic ovarian cancer mouse model. Associated cell types and pathways were explored with bioinformatics. FGF7 protein was measured using capillary-based immunoassays or ELISA in mouse and clinical specimens. Significances of differential gene expression and patient prognosis were determined by volcano plot and log-rank test, respectively.ResultsTumor transcriptomes exhibited higher endothelial cells, oxygenation, proteasome activity, and metabolism in comparison to ascites, but similar percentages of cancer-associated fibroblasts and immune cells. FGF7 mRNA was significantly higher in mouse tumors compared to ascites. FGF7 protein was significantly higher in tumors than in ascites in independent mouse models and clinical specimens. Serum FGF7 protein levels above the median of 25 patients with ovarian cancer were associated with worse progression-free and overall survival (p = 0.005 and 0.019, respectively) independent of patient and tumor characteristics.ConclusionsIn comparison to ascites, tumors exhibit different transcriptomic profiles that identify candidate biomarkers and drug targets for predicting and preventing recurrence. Among these, elevated tumoral FGF7 validated at the protein level and elevated serum FGF7 were significantly associated with worse patient survival. These results support further development of FGF7 receptor-targeted drugs and serum FGF7 to prevent and predict recurrence, respectively.